Current issues and challenges on functional food - Corina, Ene (Economics of Agriculture, 2010)
The article sets out the key-details in the field of functional foods, featuring their current role and relevance, which are based on their functions and associated benefits. It also lays down a wide range of issues and key-challenges - related to both consumers and producers - whose approach will determine the future trend line for this sector of food production. The paper shows a series of important elements to be taken into account by governments, experts, sellers and consumers so that the integration of functional food in human nutrition has a positive effect on health and nutritional welfare.